Sistem Pakar Diagnosis Penyakit Pada Tanaman Jeruk Manis dengan Metode Dempster Shafer - fitriani, eka; aldo, Dasril (Jurnal Sains dan Informatika, 2019)
Orange plants are plants that are cultivated by farmers. This study aims to assist farmers in diagnosing the disease of sweet orange plants using the Dempster Shafer method. Calculating the trust value of the selected symptoms by comparing each weight value of the 2 initial symptoms selected then compared with the weight values of other symptoms so that new symptoms that lead to a disease are produced accompanied by the value of their beliefs. Keywords:Expert System, Dempster Shafer, Orange plant disease